2011
DOI: 10.1128/jvi.00760-11
|View full text |Cite
|
Sign up to set email alerts
|

Rous Sarcoma Virus Gag Has No Specific Requirement for Phosphatidylinositol-(4,5)-Bisphosphate for Plasma Membrane Association In Vivo or for Liposome Interaction In Vitro

Abstract: The MA domain of the retroviral Gag protein mediates interactions with the plasma membrane, which is the site of productive virus release. HIV-1 MA has a phosphatidylinositol-(4,5)-bisphosphate [PI(4,5)P 2 ] binding pocket; depletion of this phospholipid from the plasma membrane compromises Gag membrane association and virus budding. We used multiple methods to examine the possible role of PI(4,5)P 2 in Gag-membrane interaction of the alpharetrovirus Rous sarcoma virus (RSV). In contrast to HIV-1, which was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 68 publications
3
80
1
Order By: Relevance
“…Besides using full-length Gag (as opposed to the MA domain in our study), these experiments also contained a host of proteins from the reticulocyte lysate. Another flotation study of HIV Gag reported that PI(4,5)P 2 or PS enhances liposome binding to similar extent (59).…”
Section: Discussionmentioning
confidence: 99%
“…Besides using full-length Gag (as opposed to the MA domain in our study), these experiments also contained a host of proteins from the reticulocyte lysate. Another flotation study of HIV Gag reported that PI(4,5)P 2 or PS enhances liposome binding to similar extent (59).…”
Section: Discussionmentioning
confidence: 99%
“…Myristoylated full-length Gag synthesized in reticulocyte lysates does not bind negatively charged liposomes containing PS at the physiological concentration of this acidic lipid (Ďł30%) (12,19,20). Even at higher concentrations (Ďł50%), palmitoyl-oleoyl-PS (POPS), the most abundant form of PS in viral and plasma membranes (21), does not support efficient liposome binding although di-oleoyl-PS does (20).…”
mentioning
confidence: 99%
“…Thus, RNAs and notably gRNA may act as negative regulators of nonspecific membrane binding, likely by reducing the electrostatic interactions of the HBR with acidic lipids and preventing myristate exposure (62,63). Phosphatidylinositol-(4,5)-bisphosphate [PI(4,5)P 2 ] and probably other phosphoinositides (64,65), which are essentially found on the cytoplasmic leaflet of the PM, can outcompete gRNA (61,66) and promote the anchoring of the myristoylated MA domain to the PM (62,67). The PI(4,5)P 2 -induced release of GagMA from the gRNA is also thought to promote Gag trimerization and a structural switch of Gag to its rodshaped conformation that is observed in virus particles (68)(69)(70).…”
mentioning
confidence: 99%